Effect of cumin (Cuminum cyminum) seed supplementation on production performance, nutrient digestibility and haemato-biochemical profile of Mehsana goats - MODI, C P; PATIL, S S; PAWAR, M M; CHAUDHARY, A B; Chauhan, H D; Ashwar, B K (The Indian Journal of Animal Sciences, 2022)
A study was carried out to investigate the effect of supplementation of cumin (Cuminum cyminum) seed (CS) on the production performance, nutrient digestibility and hemato-biochemical profiles of lactating Mehsana goats. Twenty lactating Mehsana goats (7 days post-partum) were assigned randomly into two groups (10 animals in each), control (CON: fed basal diet without supplement) and treatment (CS: basal diet supplemented with 10 g/animal/d of CS) for the duration of 60 days. The final body weight was significantly higher (38.09 vs. 34.04 kg) in the animals of CS group than the CON group. Feeding of cumin seed to the lactating goats did not influence daily dry matter intake. However, cumin seed supplementation increased milk yield (985 vs. 859 g/d), 4% FCM (818 vs 623 g/d) and ECM (952 vs. 742 g/d) as compared to the CON group. The percentages of milk fat, SNF, total solids and lactose were also improved by the supplementation of cumin seed. Apparent digestibility of dry matter was comparable in CON and CS groups. However, the digestibilities of crude protein (58.19 vs. 66.97%), crude fibre (47.05 vs. 55.28%), ether extract (67.00 vs.75.82%) and nitrogen free extract (65.25 vs. 75.32%) were significantly improved in cumin supplemented group. There was no effect on haematological parameters between the CON and CS groups. The supplementation of cumin has significantly improved glucose concentration in CS group when compared to the CON group. The concentrations of other estimated blood metabolites were not affected by the cumin supplementation in lactating goats. Based on the results of the present study, it can be concluded that cumin supplementation in the diet of lactating Mehsana goats at the rate of 10 g/d improved milk yield, nutrient digestibility and feed efficiency without any adverse effect on haemato-biochemical parameters